A model of innovation process of creating innovative high-tech products - J. V. Selyavsky; A. V. Oficerov (Путеводитель предпринимателя, 2020)
In this article the level of innovative process development in Russia is analyzed, the key features of innovative activity organization are revealed, a model of innovative process of creating high-tech products is proposed.